Sapphic fathers: Discourses of same-sex desire from nineteenth-century France - Schultz, Gretchen (University of Toronto romance series, 2014)
Literature that explored female homosexuality flourished in late nineteenth-century France. Poets, novelists, and pornographers, whether Symbolists, Realists, or Decadents, were all part of this literary moment. In Sapphic Fathers, Gretchen Schultz explores how these male writers and their readers took lesbianism as a cipher for apprehensions about sex and gender during a time of social and political upheaval. Tracing this phenomenon through poetry (Baudelaire, Verlaine), erotica and the popular novel (Belot), and literary fiction (Zola, Maupassant, Péladan, Mendès), and into scientific treatises, Schultz demonstrates that the literary discourse on lesbianism became the basis for the scientific and medical understanding of female same-sex desire in France. She also shows that the cumulative impact of this discourse left tangible traces that lasted well beyond nineteenth-century France, persisting into twentieth-century America to become the basis of lesbian pulp fiction after the Second World War.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires

De Marie de l'Incarnation à Nelly Arcan: se dire, se faire par l'écriture intime - Smart, Patricia (Boréal, 2014)
«Ce livre trouve son origine dans le désir d'explorer les expériences des femmes qui ont accompagné et rendu possibles les grands moments de l'histoire officielle du Québec, de l'arrivée des Français en Amérique du Nord jusqu'à l'accession à la liberté d'expression individuelle et collective apportée par la Révolution tranquille. Les historiennes féministes ont examiné la situation de ces femmes, mais il est rare que nous entendions la voix des protagonistes elles-mêmes ou que nous ayons accès à leur point de vue, que ce soit sur le monde qui les entoure ou sur leurs aventures intérieures. C'est cette voix que Patricia Smart donne à entendre ici. Tous ces textes parlent d'un moi brimé, inhibé, mais qui se refuse à démissionner. Pour ces femmes, la venue à l'écriture fait partie intégrante de la quête de soi et de la prise de possession du monde. Beaucoup plus que de simples révélateurs de réalités sociales, ces écrits intimes appartiennent à la littérature.» --Quatrième de couverture..
Keywords: amériques; arts; canada; cours; discipline; histoire et politique; lit3495; premier cycle; québec; régions géographiques; thématiques; écriture des femmes*; études littéraires